Processing of Written Sentences on the Example of Russian-English Bilinguals - LIUBOV DARZHINOVA (Indonesian Research Journal in Education |IRJE|, 2019)
Written language processing is broadly explained from the perspective of English and alongside with the other world languages. The current study views the concerned type of processing through the Russian-English linguistic combination, which is seen as having a limited research in the investigation into written language processing. By using a mixed methods research design, 21 Russian-speaking users of English were engaged in the study. The subjects filled in the questionnaire about their linguistic background followed by the participation in the experiment. The experimental setting was as follows: each subject had to classify the 240 Russian-English sentences as correct or not during the time interval of 5000 milliseconds. The results of the study conform with the BIA model, and suggest that semantic type of written language processing is more accurate than syntactic type but at around same level in time constraints.